2013
DOI: 10.1155/2013/570878
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Hill-Type Muscle and Stability: Numerical Model and Application

Abstract: The construction of artificial muscles is one of the most challenging developments in today's biomedical science. The application of artificial muscles is focused both on the construction of orthotics and prosthetics for rehabilitation and prevention purposes and on building humanoid walking machines for robotics research. Research in biomechanics tries to explain the functioning and design of real biological muscles and therefore lays the fundament for the development of functional artificial muscles. Recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
2
0
0
Order By: Relevance
“…the well-known muscle force-length-velocity dependency. These reduced models were specifically introduced to reveal the relevance of muscle properties in periodic movements, such as hopping [18,19] and confirmed previous findings that the force-length-velocity relation of muscles is significant with respect to the control of biological movements [11,13,18,49,59,60]. More precisely, neglecting the force-velocity relation results in unstable hopping with the proposed simple bio-inspired controllers in the reduced [18,19] and in more complex models [13,59].…”
Section: Discussionsupporting
confidence: 71%
“…the well-known muscle force-length-velocity dependency. These reduced models were specifically introduced to reveal the relevance of muscle properties in periodic movements, such as hopping [18,19] and confirmed previous findings that the force-length-velocity relation of muscles is significant with respect to the control of biological movements [11,13,18,49,59,60]. More precisely, neglecting the force-velocity relation results in unstable hopping with the proposed simple bio-inspired controllers in the reduced [18,19] and in more complex models [13,59].…”
Section: Discussionsupporting
confidence: 71%
“…Similar effects have been demonstrated for jumping (van Soest and Bobbert, 1993) and walking (Gerritsen et al, 1998;John et al, 2013). In conclusion, this implied that studies on neural control of biological movement should consider the biomechanical characteristics of muscle contraction (Pinter et al, 2012;Schmitt et al, 2013;Dura-Bernal et al, 2016). We also showed that a state-dependent analysis of MC leads to additional insights.…”
Section: Discussionsupporting
confidence: 80%